2013
DOI: 10.3390/ijerph110100312
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Distribution and Hotspots of Hand, Foot and Mouth Disease (HFMD) in Northern Thailand

Abstract: Hand, Foot and Mouth Disease (HFMD) is an emerging viral disease, and at present, there are no antiviral drugs or vaccines available to control it. Outbreaks have persisted for the past 10 years, particularly in northern Thailand. This study aimed to elucidate the phenomenon of HFMD outbreaks from 2003 to 2012 using general statistics and spatial-temporal analysis employing a GIS-based method. The spatial analysis examined data at the village level to create a map representing the distribution pattern, mean ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 34 publications
4
66
1
Order By: Relevance
“…There are many children living together in day care center during the daytime, which is a contributing factor to the epidemic of HFMD. Samphutthanon et al [19] reported that children who lived in crowded place had a high risk to expose and get infection of HFMD in China. The study of Navarro et al [20] presented that the children who attended day care center had 14 times greater chance of getting HFMD infection than those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…There are many children living together in day care center during the daytime, which is a contributing factor to the epidemic of HFMD. Samphutthanon et al [19] reported that children who lived in crowded place had a high risk to expose and get infection of HFMD in China. The study of Navarro et al [20] presented that the children who attended day care center had 14 times greater chance of getting HFMD infection than those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…According to the figures of the Bureau of Epidemiology of the past 10 years, HFMD outbreaks occurred mainly in this region (Samphutthanon, 2014). Until now, effective chemoprophylaxis or vaccination approaches for dealing with HFMD are not available.…”
Section: Introductionmentioning
confidence: 99%
“…And the mean centers denote the area and extent of the incidence of measles cases. The linear directional mean was conducted in Arc GIS 10.0 to measure the directional trend of measles transmission in Guangxi, using the annual mean center movements of measles incidence during 2004–2014 [26]. …”
Section: Methodsmentioning
confidence: 99%